A Study on Myogenesis by Regulation of Reactive Oxygen Species and Cytotoxic Activity by Selenium Nanoparticles - Sang-Cheol Lee; Na-Hyun Lee; Kapil D. Patel; Soo-Kyung Jun; Jeong-Hui Park; Jonathan Campbell Knowles; Hae-Won Kim; Hae-Hyoung Lee; Jung-Hwan Lee (MDPI AG, 2021)
Reactive oxygen species (ROS) are continuously produced by skeletal muscle during contractile activity and even at rest. However, the ROS generated from excessive exercise or traumatic damage may produce more ROS than can be neutralized by an antioxidant capacity, which can be harmful to muscle function. In particular, selenium is a known antioxidant that regulates physiological functions such as cell differentiation and anti-inflammatory function. In this study, we developed nano-sized antioxidative biomaterials using selenium to investigate the protective and differentiation effects against C2C12 myoblasts in an H2O2-induced oxidative stress environment. The selenium nanoparticles (SeNPs) were produced with a size of 35.6 ± 4.3 nm and showed antioxidant effects according to the 3,3',5,5'-tetramethylbenzidine assay. Then, SeNPs were treated to C2C12 cells with or without H2O2. Our results showed that SeNPs reduced C2C12 apoptosis and intracellular ROS levels. Additionally, SeNPs effectively up-regulated in the presence of H2O2, MyoD, MyoG, α-actinin, and myosin heavy chain, which are well known to increase during myoblast differentiation as assayed by qRT-PCR, immunocytochemistry-staining, western blotting. These results demonstrate that SeNPs can accelerate differentiation with its protective effects from the ROS environment and can be applied to the treatment of skeletal muscle in a cellular redox environment.